MiR-6869-5p Induces M2 Polarization by Regulating PTPRO in Gestational Diabetes Mellitus. (3rd May 2021) - Wang, Pingping; Ma, Zhenzhi; Wang, Zengyan; Wang, Ximei; Zhao, Guifeng; Wang, Zengfang
Abstract : The role of microRNA (miRNA) in gestational diabetes mellitus has been widely investigated during the last decade. However, the altering effect of miR-6869-5p on immunity and placental microenvironment in gestational diabetes mellitus is largely unknown. In our study, the expression of miR-6869-5p was documented to be significantly decreased in placenta-derived mononuclear macrophages, which was also negatively related to PTPRO. Besides, PTPRO was negatively regulated by miR-6869-5p in placenta-derived mononuclear macrophages. In vitro, miR-6869-5p inhibited macrophage proliferation demonstrated by EdU and CCK-8 experiments. The inflammatory response in macrophages was also significantly inhibited by miR-6869-5p, which could regulate PTPRO as a target documented by luciferase reporter assay. Moreover, miR-6869-5p promoted M2 macrophage polarization and thus restrain inflammation. Accordingly, miR-6869-5p is involved in maintaining placental microenvironment balance by preventing from inflammation and inducing M2 macrophages in gestational diabetes mellitus.